2021
DOI: 10.3390/ijms22126522
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte Dysfunction in Joint Homeostasis and Osteoarthritis

Abstract: Structural disturbances of the subchondral bone are a hallmark of osteoarthritis (OA), including sclerotic changes, cystic lesions, and osteophyte formation. Osteocytes act as mechanosensory units for the micro-cracks in response to mechanical loading. Once stimulated, osteocytes initiate the reparative process by recruiting bone-resorbing cells and bone-forming cells to maintain bone homeostasis. Osteocyte-expressed sclerostin is known as a negative regulator of bone formation through Wnt signaling and the RA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 161 publications
(277 reference statements)
0
23
0
Order By: Relevance
“…According to the literature, the occurrence of OA depends on a variety of mechanisms. In addition to inflammatory responses, mechanical load, oxidative stress, and cell senescence may all promote the degradation and inhibit the synthesis of the extracellular matrix, resulting in cartilage damage and ultimately OA [36][37][38][39]. Therefore, early suppression of inflammatory responses in chondrocytes and mitigation of oxidative stress levels may delay the onset of OA.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, the occurrence of OA depends on a variety of mechanisms. In addition to inflammatory responses, mechanical load, oxidative stress, and cell senescence may all promote the degradation and inhibit the synthesis of the extracellular matrix, resulting in cartilage damage and ultimately OA [36][37][38][39]. Therefore, early suppression of inflammatory responses in chondrocytes and mitigation of oxidative stress levels may delay the onset of OA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has characterized early-stage OA with increased subchondral bone remodeling and late OA with decreased bone resorption and increased bone formation ( 5 ). Abnormal subchondral bone remodeling and osteophyte formation are hallmarks of OA progression ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Breakdown of cartilage and subchondral bone may allow for exchange of larger-than-normal molecules to influence signaling pathways and increase cross-talk between the normally unconnected compartments of synovium and bone marrow [19]. Studies have shown cellular fractions such as macrophages, osteoblasts, osteocytes, adipocytes, T-cells, B-cells, megakaryocytes, granulocytes, and osteoblasts found in the bone/bone marrow may affect, or be affected by, the cartilage and subchondral bone changes seen in OA joints [10][11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The degenerative changes which include thinning of cartilage layers, increase in subchondral bone content, increased underlying bone remodeling, and fissures which penetrate both cartilage and bone have been well documented [2][3][4][5][6][7][8][9]. Qualitative and quantitative studies have evaluated adipocyte, T-cell, B-cell, macrophage, megakaryocyte, granulocyte, osteoblast, osteoclast, and osteocyte activity that affects the cartilage and subchondral bone in OA [10][11][12][13][14][15][16][17][18]. The goal of the study was to evaluate the hematopoietic elements in the proximal end of the osteoarthritic femur head as they compare to hematopoietic elements in normal bone marrow aspirates collected from the traditional posterior iliac crest to determine whether the joint pressure and bone degeneration influences the underlying blood cell fractions.…”
Section: Introductionmentioning
confidence: 99%